PENGARUH KOMPLEKSITAS TUGAS, TEKANAN KETAATAN, TINGKAT SENIORITAS AUDITOR, KEAHLIAN AUDITOR, DAN HUBUNGAN DENGAN KLIEN TERHADAP AUDIT JUDGEMENT (Studi Pada Akuntan Publik di KAP Wilayah Sumatera) - Fitriana, Rahayu; ', Kamaliah; ', Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to know the influence of the complexity of the task, the pressure of obedience, the level of seniority of the auditor, the auditor's expertise, and the relationship with the clients of audit judgement.This study population is auditor working in public accounting in the area of Sumatra. These studies use SPSS software to manipulate data. Sampling method in this research is the random sampling and the total number of respondents who made a sample on this research is as much as 48% (106 people)Results of the study prove that the complexity of the task, the pressure of obedience, expertise, and relationships with influential clients of audit judgement. While the level of seniority of the auditors audit against the judgement has no effect.Keywords: the complexity of the task, the pressure of obedience, the level of seniority of the Auditor, Auditor, Expertise and relationships with clients.